Action on Poverty and Hardship in the English Potteries. (December 2022) - Goldstraw, Katy; Page, Sarah
Reflecting on anti-poverty work within Stoke-on-Trent from a variety of academic perspectives, this special edition offers a place-based examination of action on poverty and hardship that seeks to link local, creative, place-based solutions to national and international anti-poverty agendas. Each article links to how the author(s) contribute to action on poverty and hardship in the potteries and reflects on national, place based anti-poverty perspectives. The special edition holds key themes around the need for place-based longitudinal investment, the imperative to work with communities, foregrounding the knowledge held by lived experience. In conclusion, Stoke-on-Trent is a community in which many of the authors live, all of whom work and one in which Gratton (2020) articulates that the University has made an institutional commitment to work in partnership with to address poverty. The articles also demonstrate that academics working in collaboration with the anti-poverty sector including people with lived and learned experience and alongside students can achieve positive change in a city, with recognition that more can be done locally to transform lives, neighbourhoods, transport routes and wider societal economic and well-being reform.